The Fiqhi Thought of Price Volatility in Crypto Asset - Mohd Noh, Mohd Shahid (Jurnal Fiqh, 2022)
Cryptocurrency gains the popularity among digital investors almost in a decade. Starting with bitcoin or BTC as a pioneer coin in the crypto market, today there are more than five thousand different coins are being traded at every second worldwide. The acceptance among giant companies and countries had shown positive trend that this new asset class might have a bright future. Replacing fiat currency as main currency is a possible even there are too many hurdles and challenges to be solved but to be treated as an investment mode could be accepted in today’s situation. This paper aims to seek a clarification on how Shariah ruling in trading crypto asset, is it Shariah compliant? or at least Shariah-friendly especially when the digital asset always been criticized for being too volatile in their prices that deemed as gharar. As a result, cryptocurrency in general is a legal asset to be traded from Shariah view even it vulnerable to price volatility due to clarity of the transaction, market factors that create the prices and for security purposes. Besides, the trade does not contain any riba element, gharar and maysir also involve in prohibited business.